Cracking the egg: An insight into egg hypersensitivity. Issue 2 (August 2015) - Dhanapala, Pathum; De Silva, Chamika; Doran, Tim; Suphioglu, Cenk
Highlights Egg allergy is the second most common food allergy in children, next to cow's milk allergy. Egg allergy is mainly caused by hypersensitivity to four allergens found in the egg white. Egg yolk specific allergens may play a crucial role in the overall egg allergic reaction. Currently there is no permanent cure for egg allergy. An understanding of egg allergens and their prevalence is important for diagnosis and treatment.